2008
DOI: 10.1074/jbc.m701572200
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Caveolin-1, an Inhibitor of Transforming Growth Factor-β Signaling, in Acute Allergen-induced Airway Remodeling

Abstract: Asthma can progress to subepithelial airway fibrosis, mediated in large part by transforming growth factor-␤ (TGF-␤). The scaffolding protein caveolin-1 (cav1) can inhibit the activity of TGF-␤, perhaps by forming membrane invaginations that enfold TGF-␤ receptors. The study goals were 1) to evaluate how allergen challenge affects lung expression of cav1 and the density of caveolae in vivo 2) to determine whether reduced cav1 expression is mediated by interleukin (IL)-4 and 3) to measure the effects of decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 50 publications
(43 reference statements)
5
41
1
Order By: Relevance
“…High expression of TGF-, another marker for tissue remodeling, was also found during early torpor and also at early arousal, which was then reduced to the euthermic level at the late arousal phase (Fig.5B). Caveolin-1 expression, as part of the TGF- signaling pathway was also measured (Le Saux et al, 2008b). The expression was reduced to half of the euthermic expression during the late torpor phase, and it reached its highest point during early arousal (Fig.6D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of TGF-, another marker for tissue remodeling, was also found during early torpor and also at early arousal, which was then reduced to the euthermic level at the late arousal phase (Fig.5B). Caveolin-1 expression, as part of the TGF- signaling pathway was also measured (Le Saux et al, 2008b). The expression was reduced to half of the euthermic expression during the late torpor phase, and it reached its highest point during early arousal (Fig.6D).…”
Section: Resultsmentioning
confidence: 99%
“…Caveolin-1-deficient mice show lung abnormalities, with thickened alveolar septa and hypercellularity, and they are exercise intolerant (Razani et al, 2001). Caveolin-1 inhibits the activity of TGF-, perhaps by forming membrane invaginations that enfold TGF- receptors (Le Saux et al, 2008a); however, a higher expression of TGF- has shown to downregulate caveolin-1 expression in cultured endothelial cells (Igarashi et al, 2009). In our experiment lower expression of caveolin-1 was accompanied by higher expression of TGF- as a remodeling marker.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were maintained at 37°C, and culture supernatants were collected after 96 h for the quantification of OVA-specific IgE by sandwich ELISA (Serotec) as described above. Ferric Reducing Ability Assay and Poly(ADP-ribosyl)ation in Vitro-The ferric reducing ability of minocycline was measured essentially as described previously (22). The antioxidant capacity of minocycline was calculated from the linear calibration curve and expressed as mmol FeSO4 equivalents.…”
Section: Production Of Ova-specific Ige By B Cells-ova-sensitized B Cmentioning
confidence: 99%
“…The physiological importance of cav1 in lungs has recently been highlighted by the description of its dysregulation in pulmonary disorders such as interstitial fibrosis (48) and bronchiolization in lung fibrosis (29,43) and in airway remodeling in an allergen-challenged mouse model (23). In these pathologies, decreased expression of the gene encoding cav1 (cav1) was associated with enhanced TGF-␤ signaling and increased collagen deposition.…”
mentioning
confidence: 99%